The social and spatial insularity of internally displaced persons: "neighbourhood effects" in Georgia's collective centres. Issue 2 (4th May 2019) - Gogishvili, David; Harris-Brandts, Suzanne
ABSTRACT: Since 1991, armed conflicts in regions of Georgia have forced over 300, 000 people to become internally displaced persons (IDPs). Many settled on the outskirts of cities in state-provided, non-residential buildings called collective centres, which function as distinct neighbourhoods with their spatial segregation and community networks. This article charts the impacts of social and spatial insularity on IDPs in these centres and frames it within the concept of neighbourhood effects. Research on neighbourhood effects has shown that physical and social isolation can exacerbate issues of health, education, living conditions, and employment, present in particular areas. Although IDPs are a vulnerable, socio-economically disadvantagedpopulation often living in concentrated poverty, to date this concept has not been applied to their conditions. This article addresses that gap by examining the neighbourhood effects of collective centres. The work provides a meta-analysis of existing research on Georgian IDPs and complements it with two years of first-hand data collected through a representative survey. The results show that IDPs within Georgia are at multiple disadvantages as a result of their isolation in collective centres. The article concludes with a call for greater government consideration of IDP isolation in situations of protracted conflict, so as to resist such detrimental effects.